2008
DOI: 10.4049/jimmunol.181.1.768
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Antibody and T Cell-Specific Responses to the Progression of 139A-Scrapie in C57BL/6 Mice Immunized with Prion Protein Peptides

Abstract: Prion diseases are associated with the conversion of the normal host cellular prion protein to an abnormal protease-resistant (PrPres) associated with infectivity. No specific immune response against prions develops during infection due to the strong tolerance to cellular prion protein. We examined the protective potential on prion diseases of immune responses elicited in C57BL/6 mice with PrP peptides 98–127 (P5) or 158–187 (P9) with CpG. After immunization, P5-treated mice developed high titer and long-lasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…infection and extended survival by 16 days compared with controls. Active immunization with PrP 98-127 or PrP 158-187 in the presence of CpG induced T cells and Ab production but prolonged mouse survival by only 20 days (Sacquin et al, 2008). More encouraging results have been obtained by Goni et al (2008) following oral immunization with Salmonella typhimurium encoding one or two copies of mouse Prnp in their genome.…”
Section: Discussionsupporting
confidence: 50%
“…infection and extended survival by 16 days compared with controls. Active immunization with PrP 98-127 or PrP 158-187 in the presence of CpG induced T cells and Ab production but prolonged mouse survival by only 20 days (Sacquin et al, 2008). More encouraging results have been obtained by Goni et al (2008) following oral immunization with Salmonella typhimurium encoding one or two copies of mouse Prnp in their genome.…”
Section: Discussionsupporting
confidence: 50%
“…Tregs are probably not imported within the cohort of T cells that comes from PrP-deficient donors, but they may develop in PrP-sufficient hosts and may affect nonboosted T cells more heavily than regularly challenged T cells. A recent study from our laboratory demonstrated the development of such regulatory T cells, notably when mice were infected with 139A (55).…”
Section: Discussionmentioning
confidence: 99%
“…Ab against PrPc was measured using a previously described immunofluorescence assay on transfected EL4 cells overexpressing PrPc (50,55). Fig.…”
Section: Absence Of Significant Ab Response In Recipients Of Primed Lmentioning
confidence: 99%
See 1 more Smart Citation
“…The same Ad168NP immunization procedure performed with 139A-incubating mice is not associated with an extended clinical phase. We showed previously that PrP 158-197 -specific CD4 + T cell responses were blunted when immunization was performed in 139A-incubating mice (Sacquin et al, 2008). In vivo and in vitro depletion of CD4 + CD25 + T cells completely restores the in vitro T-cell response to PrP , suggesting the development of an immune regulatory mechanism during prion accumulation.…”
Section: Discussionmentioning
confidence: 83%